Stock price fluctuation based on mobile computing. (2017) - Du, Zhanqi; Wang, Hongwei; Wang, Shiming; Zhang, Lizhen; Gao, Song; Guo, Kaiqiang
Mobile computing, a relatively mature technique in the field of interactive mobile internet system, is widely used for forecasting the spatial locations and movements of user. This paper takes the stock price fluctuation as the location changes of mobile object, analyses the fluctuation features of stock price and proposes the forecasting model of stock price based on the mobile computing and local linear method. Taking stock S as an example in the Shanghai and Shenzhen stock markets, the paper collects a large amount of data and simulates the forecasting model of intraday stock price and daily closing price. Finally, the experiment results show that this model has good forecast precision and applicability.